2014
DOI: 10.1021/pr500506z
|View full text |Cite
|
Sign up to set email alerts
|

Confident Assignment of Site-Specific Glycosylation in Complex Glycoproteins in a Single Step

Abstract: A glycoprotein may contain several sites of glycosylation, each of which is heterogeneous. As a consequence of glycoform diversity and signal suppression from nonglycosylated peptides that ionize more efficiently, typical reversed-phase LC–MS and bottom–up proteomics database searching workflows do not perform well for identification of site-specific glycosylation for complex glycoproteins. We present an LC–MS system for enrichment, separation, and analysis of glycopeptides from complex glycoproteins (>4 N-gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 34 publications
1
66
0
Order By: Relevance
“…Additionally, glycosylated peptides often ionize poorly relative to non-glycosylated peptides [12]. In order to characterize a glycoproteome in detail, a MS workflow typically requires an efficient enrichment platform, a high-throughput MS analysis, and algorithms for targeted glycoproteomics [13,14]. To this end, a number of MS workflows have been established for confident discovery and identification of complex mixtures of glycopeptides [1319].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, glycosylated peptides often ionize poorly relative to non-glycosylated peptides [12]. In order to characterize a glycoproteome in detail, a MS workflow typically requires an efficient enrichment platform, a high-throughput MS analysis, and algorithms for targeted glycoproteomics [13,14]. To this end, a number of MS workflows have been established for confident discovery and identification of complex mixtures of glycopeptides [1319].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, IdeS and other enzymes for limited proteolysis generating larger peptides for a faster middle-up glycoprofiling were successfully applied for lot variability and biosimilar analysis of mAbs via LC-ESI-(Q)TOF-MS [44,50]. C 18 -RP materials commonly used for bottom-up proteomics may not retain certain glycopeptides due to increased analyte hydrophilicity compared to non-glycosylated peptides, requiring additional use of porous graphitize carbon (PGC) [41] or HILIC [51]. HILIC separation of glycopeptides is based on the properties of the peptide and the glycan moiety, and tolerates various substitutions, such as sulfation [52].…”
Section: Lc-esi-ms and Lc-ms/msmentioning
confidence: 99%
“…HILIC separation of glycopeptides is based on the properties of the peptide and the glycan moiety, and tolerates various substitutions, such as sulfation [52]. A recent approach demonstrated that on-line HILIC pre-enrichment of N-glycopeptides prior to C18-LC-QTOF-MS/MS resulted in efficient site-specific glycoprofiling [51]. The detection of both glycan and peptide fragmentation in the same MS/MS spectrum via elevated-energy CID allowed confirmation of both peptide and glycan sequence, and site assignment.…”
Section: Lc-esi-ms and Lc-ms/msmentioning
confidence: 99%
See 1 more Smart Citation
“…MS, combined with efficient separation techniques, has become a powerful tool for structural analysis of carbohydrates [59]. Some of its advantages include low sample consumption and high sensitivity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%